Cisco security professional's guide to secure intrusion detection systems - Burton, James D.; Dubrawsky, Ido; Osipov, Vitaly; Baumrucker, C. Tate (Syngress Publishing, 2003)
Cisco Systems, Inc. is the worldwide leader in networking for the Internet, and its Intrusion Detection Systems line of products is making in roads in the IDS market segment, with major upgrades having happened in February of 2003. A comprehensive, up-to-date guide to the hardware and software that comprise the Cisco IDS. This book does more than show network engineers how to set up and manage this line of best selling products ... it walks them step by step through all the objectives of the Cisco Secure Intrusion Detection System course (and corresponding exam) that network engineers must pas.